Warthin Tumor-Like Papillary Thyroid Carcinoma with a Minor Dedifferentiated Component: Report of a Case with Clinicopathologic Considerations - Paolo Amico; Salvatore Lanzafame; Giovanni Li Destri; Paolo Greco; Rosario Caltabiano; Giada Maria Vecchio; Gaetano Magro (Case Reports in Medicine)
Warthin tumor-like papillary thyroid carcinoma is an uncommon variant of papillary thyroid carcinoma. We report a rare case of Warthin tumor-like variant of papillary thyroid carcinoma with a dedifferentiated component consisting of a solid tumor area composed of neoplastic cells with a spindle to tall cell morphology associated with marked nuclear pleomorphism, atypical mitoses, and foci of necrosis. Although our patient presented with a locally aggressive disease (T3 N1b Mo), she is disease-free without radioiodine therapy after a 23-month follow-up period. We emphasize that Warthin tumor-like papillary thyroid carcinoma, like other morphological variants of papillary carcinoma, may occasionally undergo dedifferentiation. As this component may be only focally detectable, we suggest an extensive sampling of all large-sized (>3 cm) papillary thyroid carcinoma. Recognition of any dedifferentiated component in a Warthin tumor-like papillary thyroid carcinoma should be reported, including its percentage, because it may reflect a more aggressive clinical course.